SCALE EFFECT AND SELECTION EFFECT AFTER POLAND’S ACCESSION TO THE EUROPEAN UNION. - Chilimoniuk-Przeździecka, Eliza (Ekonomia i Prawo. Economics and Law, 2012)
The last seven years have brought about significant changes in the Polish economy. Market openness means above all the benefits of higher production, and market expansion. This implies, however, with a decrease in the number of companies that fail to deal with the incoming of foreign competition. As a result of opening the market, we are dealing with two opposing effects - the scale effect, as firms expand their outputs, and the selection effect, as some firms are forced to exit due to the pressure of foreign competition. The study identifies a scale effect in these industries, which increased revenue, export sales, and the number of firms. In turn, the selection effect was identified on the basis of the decrease in the number of firms in 2004-2010 and improvement of the profitability ratio. The evaluation of these two effects reflects the impact of opening the economy to the functioning of manufacturing companies.